Vogalna singularnost torzije kompozitne palice - Mejak, George (Strojniški vestnik, 2002)
The material matrix of composite materials is constant for each individual component. This discontinuity sets regularity bounds upon the solution. Besides material discontinuities, the regularity of the solution is also affected by geometrical singularities along the material interfaces. If the interface has corners, we speak about corner singularities of the composite. Mechanical manifestations of these singularities are stress concentrations. One of the most important pieces of information about the corner singularity is the order of the singularity. In this article a method for determining the order of the singularity for the model problem if a composite bar in torsion is presented. In the first part a model of torsion for a composite bar with perfect and imperfect bonds is given. For a perfect interfacial bond the existence of the corner stress concentration is proved by the asymptotical method. The order of the singularity with respect to the angle of the corner and the material constants is explicitly computed. It is found that the order is independent of the material orientation in the corner. For the case of an imperfect bond the existence of the stress concentration is established for a weak bond. The existence is proved by the regular asymptotic perturbation of the nomaterial adhesion.
Keywords: kompoziti; palice; problemi modeliranja; analize singularnosti; torzija; matematični modeli